2016
DOI: 10.1111/jocn.13341
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating medical errors made by nurses during their diagnosis, treatment and care practices

Abstract: The results of this study could be used to take precautions against nursing medical errors in Turkey and to enhance institutional policies and activities regarding medical errors and patient safety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
1
13

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 19 publications
0
36
1
13
Order By: Relevance
“…It was reported that there is an increasing rate of medical error committed by nurses. Medical errors have recently emerged as a significant issue as they result to death and disability of patients each year [6]. Other literatures that explore medication administration error recurrently relates inaccuracies to certain professional characteristics, attributes, skills and competencies [7].…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that there is an increasing rate of medical error committed by nurses. Medical errors have recently emerged as a significant issue as they result to death and disability of patients each year [6]. Other literatures that explore medication administration error recurrently relates inaccuracies to certain professional characteristics, attributes, skills and competencies [7].…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the results on KPIs signify its connection with some researches' findings where safety in the hospital's clinical environment obtained a positive remark (Paguio and Pajarillo, 2016). This is in contrast, however with the study of Kahriman and Öztürk (2016) revealed the 1,092 nurses' experience on medical errors due to fatigue, communication barriers and insufficient staffing levels.…”
Section: Discussionmentioning
confidence: 82%
“…At a particular note, nurses must always assess and achieve a safe working environment for patients to prevent errors related to medication and blood transfusion, falls, pressure sores and nosocomial infections (Arnetz et al, 2019;Ricklin et al, 2019;Shang et al, 2019). A high safety competency grade creates a positive influence on patients' overall safety due to enhanced teamwork, workshops and processes (Choi et al, 2019;Jin and Yi, 2019;Kahriman and Öztürk, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current study results showed that clinical errors are affected both by individual factors (satisfaction rate, displacement, and staff absence) and systemic factors (training costs, bed occupation, and length of stay average and hospital infections). In general, the reasons for medical errors are put into three groups: human factors like the exhaustion, inadequate training and neglect; organizational factors like the policies, structures of the work place, and unsuitable distribution of personnel; and technical factors such as insufficient automation, insufficient instruments, and inefficient equipment (44).…”
Section: Internal Processes Perspectivementioning
confidence: 99%